2016
DOI: 10.1016/j.ijsu.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of conventional MRI for preoperative diagnosis of intracranial tumors: A retrospective cohort study of 762 cases

Abstract: The accuracy of conventional MRI for diagnosing intracranial tumors is generally satisfactory but should not be too heavily relied upon, especially for certain tumor types. In cases of discrepancy, neurosurgeons are encouraged to confer with the reporting neuroradiologists to achieve optimal preoperative diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
2
23
1
Order By: Relevance
“…However, the poor quality of MR images compound with the shortage of experienced radiologists make the manual analysis of MRI data difficult, biased and time-consuming. It has been reported that the current diagnostic sensitivity for primary and recurrent pituitary microadenoma is only 47% and 39%, respectively [5,6] . Therefore, an accurate and efficient auxiliary diagnostic method for the diagnosis of pituitary microadenomas is highly needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the poor quality of MR images compound with the shortage of experienced radiologists make the manual analysis of MRI data difficult, biased and time-consuming. It has been reported that the current diagnostic sensitivity for primary and recurrent pituitary microadenoma is only 47% and 39%, respectively [5,6] . Therefore, an accurate and efficient auxiliary diagnostic method for the diagnosis of pituitary microadenomas is highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality MR images are critical for the accurate diagnosis of pituitary adenoma. The increased use and accessibility of imaging techniques and improved spatial resolution of modern devices has led to a rise in incidental detection of pituitary microadenomas [3,6,18] . Importantly, accurate diagnosis of pituitary microadenoma is largely relied on the radiologist's professional experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capabilities of our proposed methodology is tested against a real-world application, namely, a brain tumour MRS data, with the purpose of elucidating and understanding the associations between brain tumour types and a range of observed metabolites. Improving the knowledge and understanding of these associations is a relevant matter, since the anatomical information provided by magnetic resonance imaging (MRI) is not always accurate, especially in case of heterogeneous, glial tumours [ 22 24 ]. Although high resolution magnetic resonance techniques with tumour samples are described in the literature for validating in vivo MRS findings [ 25 , 26 ], this requires invasive (surgical) obtention of additional samples from patients, since tissue used for histopathology analysis is not suitable.…”
Section: Datamentioning
confidence: 99%
“…The current gold standard investigation for patients with a suspected brain tumour is MRI, however determining the exact brain tumour type is not possible from imaging alone [ 5 , 6 ]. Some brain tumours pose particular imaging challenges, e.g.…”
Section: Introductionmentioning
confidence: 99%